The potent bisphosphonate ibandronate does not induce myeloma cell apoptosis in a murine model of established multiple myeloma. - Shipman, C; Vanderkerken, K; Rogers, M; Lippitt, J; Asosingh, K; Hughes, D; Van Camp, B; Russell, R; Croucher, P (2000)
Bisphosphonates are effective in the management of bone disease in patients with multiple myeloma and recent reports have suggested that they may also have an anti-tumour activity. In support of this, we have previously demonstrated that bisphosphonates can induce myeloma cell apoptosis in vitro; however, it remains unclear whether this occurs in vivo. We have therefore investigated the effect of the potent bisphosphonate ibandronate in the 5T2MM murine model of established multiple myeloma. Short-term treatment with a high dose of ibandronate had no effect on either myeloma cell number or the proportion of myeloma cells undergoing apoptosis. These observations suggest that although bisphosphonates induce apoptosis in myeloma cells in vitro, they may not have the same anti-tumour effects in vivo.